Analisis Pengaruh Variabel Makroekonomi Terhadap Nilai Tukar : Kasus Perekonomian Indonesia - Cellin Nofrina Lova; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to analyze the effect of macroeconomic variables on theexchange rate: The case of the Indonesian economy. The data used in thisstudy is time series data for the period 1990-2020 which is sourced from theWorld Bank. Analysis is used analysis Ordinary Least Square (OLS). Theresults of this study showed that (1) the variable of international trade has apositive relationship and significant effect on the exchange rate (2) thevariable of inflation has a positive relationship and significant effect on theexchange rate (3) the variables of economic has a negative and significantrelationship on the exchange rate. While the variable of loan interest rate hasa negative relationship but does not have a significant effect on the exchangerate.